Spring-assisted posterior vault expansion—a single-centre experience of 200 cases - Breakey, R. William F.; van de Lande, Lara S.; Sidpra, Jai; Knoops, Paul M.; Borghi, Alessandro; O’Hara, Justine; Ong, Juling; James, Greg; Hayward, Richard; Schievano, Silvia; Dunaway, David J.; Jeelani, N ul Owase (Child's nervous system, 2021)
Purpose Children affected by premature fusion of the cranial sutures due to craniosynostosis can present with raised intracranial pressure and (turri)brachycephalic head shapes that require surgical treatment. Spring-assisted posterior vault expansion (SA-PVE) is the surgical technique of choice at Great Ormond Street Hospital for Children (GOSH), London, UK. This study aims to report the SA-PVE clinical experience of GOSH to date. Methods A retrospective review was carried out including all SA-PVE cases performed at GOSH between 2008 and 2020. Demographic and clinical data were recorded including genetic diagnosis, craniofacial surgical history, surgical indication and assessment, age at time of surgery (spring insertion and removal), operative time, in-patient stay, blood transfusion requirements, additional/secondary (cranio)facial procedures, and complications. Results Between 2008 and 2020, 200 SA-PVEs were undertaken in 184 patients (61% male). The study population consisted of patients affected by syndromic (65%) and non-syndromic disorders. Concerns regarding raised intracranial pressure were the surgical driver in 75% of the cases, with the remainder operated for shape correction. Median age for SA-PVE was 19 months (range, 2–131). Average operative time for first SA-PVE was 150 min and 87 for spring removal. Median in-patient stay was 3 nights, and 88 patients received a mean of 204.4 ml of blood transfusion at time of spring insertion. A single SA-PVE sufficed in 156 patients (85%) to date (26 springs still in situ at time of this analysis); 16 patients underwent repeat SA-PVE, whilst 12 underwent rigid redo. A second SA-PVE was needed in significantly more cases when the first SA-PVE was performed before age 1 year. Complications occurred in 26 patients with a total of 32 events, including one death. Forty-one patients underwent fronto-orbital remodelling at spring removal and 22 required additional cranio(maxillo)facial procedures. Conclusions Spring-assisted posterior vault expansion is a safe, efficient, and effective procedure based on our 12-year experience. Those that are treated early in life might require a repeat SA-PVE. Long-term follow-up is recommended as some would require additional craniomaxillofacial correction later in life.